2015
DOI: 10.1371/journal.pone.0132182
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effectiveness of Antiretroviral Therapy in Preventing HIV Infection in Serodiscordant Couples in Uganda: An Observational Study

Abstract: BackgroundWe examined the real-world effectiveness of ART as an HIV prevention tool among HIV serodiscordant couples in a programmatic setting in a low-income country.MethodsWe enrolled individuals from HIV serodiscordant couples aged ≥18 years of age in Jinja, Uganda from June 2009 – June 2011. In one group of couples the HIV positive partner was receiving ART as they met clinical eligibility criteria (a CD4 cell count ≤250 cells/ μL or WHO Stage III/IV disease). In the second group the infected partner was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…The HAARP study compared HIV incidence between HIV negative members of serodiscordant partners who were or were not receiving ART during the study and was conducted from June 2009 to December 2011. The study did not find a benefit from ART in terms of preventing HIV seroconversion in the negative participant [27]. As a result of these findings, we enrolled a selection of previous study participants in a qualitative sub-study for a series of in-depth interviews beginning in June 2013 and continuing until August 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The HAARP study compared HIV incidence between HIV negative members of serodiscordant partners who were or were not receiving ART during the study and was conducted from June 2009 to December 2011. The study did not find a benefit from ART in terms of preventing HIV seroconversion in the negative participant [27]. As a result of these findings, we enrolled a selection of previous study participants in a qualitative sub-study for a series of in-depth interviews beginning in June 2013 and continuing until August 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this study were obtained from the Highly Active Antiretroviral therapy as Prevention (HAARP) study, an observational cohort investigating the effectiveness of antiretroviral therapy (ART) in preventing HIV transmission among sero-discordant couples in Jinja, Eastern Uganda (June 2009–June 2011) 6. Polygynous couples (where the male participant has more than one female spouse) were excluded from this analysis to avoid misclassification bias.…”
Section: Methodsmentioning
confidence: 99%
“…Third, as suggested by the aforementioned studies in rural China 12 and rural Uganda, 13 treatment as prevention will function only if people have access to care. When such access is limited, HIV viral loads cannot be monitored, sexually transmitted infections cannot be treated, important psychosocial factors cannot be addressed, and the outcome may be a similar rate of HIV transmission, irrespective of antiretroviral therapy use.…”
Section: What Factors Affect Treatment As Prevention?mentioning
confidence: 99%
“…13 Reported condom use was 51% and 67% among those receiving and not receiving antiretroviral therapy, respectively. 13 Birungi and colleagues 13 concluded that a number of factors influence HIV transmission and that, in the absence of routine monitoring and access to HIV care, these factors appear to reduce the prevention benefits of treatment as prevention.…”
Section: Does All Evidence Support Treatment As Prevention?mentioning
confidence: 99%
See 1 more Smart Citation